SOLIDARITAS DI MASA PANDEMI: PERSPEKTIF KRITIKAL TEOLOGI BISNIS - Katarina Leba; Balthasar Watunglawar (Lembaga Penelitian STKIP Widya Yuwana, 2023)
This study aims to analyze and describe the form of solidarity of business actors in the era of the covid-19 pandemic and the factors that influence solidarity. Data were collected through documentation and interview techniques. Problems which are related to appreciation and solidarity were analyzed theoretically from the perspective of business theology by using a qualitative research method approach. The results of the study inform that the solidarity of business people was reduced during the covid-19 pandemic. People were more concerned with personal safety and business continuity than the safety of others. The improvement of the welfare of the stakeholders was maintained and prioritized over the welfare of the employees. Sense of social responsibility was decreased. Employees were not considered a valuable asset that must be cared for and saved. The sense of family and togetherness was reduced. Egoism and greed were capital for business people to survive the COVID-19 pandemic. Therefore, the sense of sacrifice, love, responsibility, and a sense of kinship which are the basic principles of social solidarity need to be revived and lived by business people to achieve social welfare as exemplified by Jesus by loving humans. Jesus has willing to sacrifice himself on the cross for the salvation of mankind.